Expression of Prolactin Receptor on the Surface of Quail Spermatozoa - Hiyama, Gen (J Poult Sci, 2016)
Prolactin receptor (PRLR) is expressed in a wide variety of tissues and mediates diverse biological actions of prolactin (PRL). In mammals, PRL signaling is thought to be involved not only in the process of spermatogenesis and steroidogenesis in the testis, but also in the survival of ejaculated sperm. In avian species, although the expression of PRLR with several variants in the testis was reported, the role of PRL in testicular function is still unclear. The aim of this study was to examine the expression of PRLR in the testis and mature sperm in quail. It is revealed that PRLR was mainly localized in the round- and elongated-spermatid by immunohistochemical analysis on the testis suggesting that PRL signaling may participate in the spermatogenesis. Western blot analysis confirmed the presence of PRLR in the plasma membrane of the ejaculated sperm (SPML), whereas the size of PRLR in the sperm was smaller than that in the hypothalamus. Moreover, PRLR was detected on the surface of the midpiece and flagellum of sperm by immunostaining. To evaluate the functionality of the sperm PRLR, the dot blot assay was performed to test the binding of pituitary PRL to PRLR in the SPML, and resulted in the detection of specific binding of PRL to the component of SPML, most likely to sperm PRLR. Furthermore, when the ejaculates were incubated with pituitary PRL to investigate the role of PRL on the sperm, the occurrence of spontaneous acrosome reaction was significantly decreased. In addition, the expression of PRL on the surface of utero-vaginal junction of oviduct was detected by immunohistochemistry. These results may suggest a novel system that the interaction between oviductal PRL and sperm PRLR is involved in the maintenance of the fertilizability of the spermatozoa through the prevention of the spontaneous acrosome reaction in Japanese quail.